Die verletzte Republik Erzählte Gewalt im Frankreich des 21. Jahrhunderts - Lenz, Markus Alexander (MIMESIS, 2022)
This study examines the literary discourse about forms of violence in French society at the beginning of the twenty-first century. How and why does French contemporary literature tell stories about the now historical, violent traumas of the twentieth century, the terrorism of the twenty-first century, racism and classicism, femicide and homophobia, and the structural violence of unemployment and poverty?